Kendala Pemerintah Nagari Alang Rambah Tapan dalam Upaya Mitigasi Bencana Banjir - Khairun Nisak, Sintya; Alhadi, Zikri (PUBLICNESS: Journal of Public Administration Studies, 2024)
Frequent floods in Nagari Alang Rambah Tapan from 2020 to 2024 have caused significant losses, especially to plantation land, public facilities, infrastructure, livestock, and residential areas. In 2023, the impact of flooding reached its peak with significant losses. This research aims to explain the difficulties faced by the Government of Nagari Alang Rambah Tapan in dealing with flood disasters. This research uses a qualitative method with a descriptive approach, and informants were selected through a purposive sampling technique. Data were collected through interviews, observations, and documentation studies. The results showed various obstacles faced in flood disaster mitigation efforts, both internal and external. These constraints include limited budget or funds, the need for more authority from the village government in directing the use of Village Funds for disaster mitigation, and limitations in preparing mitigation tools. In addition, the lack of professional human resources in the disaster field, as well as inadequate facilities and infrastructure or disaster equipment, also became significant obstacles in the mitigation efforts carried out.